Co‐development of Crystalline and Mesoscopic Order in Mesostructured Zeolite Nanosheets1. (24th November 2014) - Messinger, Robert J.; Na, Kyungsu; Seo, Yongbeom; Ryoo, Ryong; Chmelka, Bradley F.
Abstract Mesoporous zeolites are a new and technologically important class of materials that exhibit improved diffusion and catalytic reaction properties compared to conventional zeolites with sub‐nanometer pore dimensions. During their syntheses, the transient developments of crystalline and mesoscopic order are closely coupled and challenging to control. Correlated solid‐state NMR, X‐ray, and electron microscopy analyses yield new molecular‐level insights on the interactions and distributions of complicated organic structure‐directing agents with respect to crystallizing zeolite frameworks. The analyses reveal the formation of an intermediate layered silicate phase, which subsequently transforms into zeolite nanosheets with uniform nano‐ and mesoscale porosities. Such materials result from coupled surfactant self‐assembly and inorganic crystallization processes, the interplay between which governs the onset and development of framework structural order on different length and time scales.